Evaluation of serum Chemerin level in non-diabetic, Hemodialized patients - M. Hussain Al-Obaidi, Saad; S. Ahmed, Salam; H. Ahmed Al-Obaidi, Amina (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Chronic Renal Failure (CRF) or chronic kidney disease (CKD) is the state which resultsfrom a permanent and usually progressive reduction in renal function and leads to many complicationsover a period of time. The most common complications include cardiovascular, cerebrovascular andperipheral vascular diseases. Most common causes of CRF are diabetes mellitus (diabetic nephropathy)and hypertention. Adipose tissue is now considered as an active endocrine gland secretes manymetabolically active adipocytokines such as chemerin, visfatin, resistin and others that have importantroles in complications and progression of metabolic diseases such as diabetes mellitus and other diseaseslike CRF and cardiovascular diseases (CVD). Aim: The aim of this study was to evaluate serum chemerinlevel and other biochemical and clinical markers in non-diabetic hemodialized patients, to determine therisk of CVD in non diabetic hemodialyzed patients. Materials and methods: This study was conductedfor a sample composed of 50 patients with end stage renal disease (ESRD) or on hemodialysis (HD) and acontrol group consists of 50 apparently normal healthy subjects. Estimation of serum chemerin level byELIZA, lipid profile, Blood urea, serum creatinine, serum albumin, serum electrolytes, serum uric acidand serum malondialdehyde (MDA) were done for both patients and control. Body mass index (BMI) andglomerular filtration rate (GFR) were calculated for both patients and control. Atherogenic index, CADrisk %, were also calculated for both HD patients and control. Results: The results of this study showedthat the level of serum chemerin was significantly increased in CKD patients on hemodialysis comparedto control. Blood urea, creatinine , TG, T-C, LDL-C,VLDL-C, MDA, uric acid, K+, BMI and atherogenicindex of plasma (AIP) levels were significantly increased in diabetic nephropathy patients compared tocontrol, while, HDL-C, CAD risk %, Na+, Ca+2, PCV%, Hb and albumin levels were significantlydecreased in ESRD patients compared to control. There was a non- significant difference of bloodglucose for HD patients and control.